Does the pursuit of outreach consistently stifle the financial performance of microfinance institutions in sub-Saharan Africa?. Issue 3 (2nd April 2020) - Chikalipah, Sydney
ABSTRACT: This article studies the relationship between outreach and the financial performance of 479 microfinance institutions (MFIs) in 37 countries of sub-Saharan Africa (SSA), covering the period 1998–2012. Findings indicate a positive and statistically significant relationship between outreach and the financial performance among MFIs in SSA. Providing small microcredits below the US600 threshold is associated with lower profitability than larger loans, and MFIs serving more than 30, 000 clients reported a stronger financial performance than those serving fewer than 30, 000. The study findings have implications for managers and stakeholders in the microfinance industry of SSA.